Reimagining consumer involvement: Resilient system indicators in the COVID‐19 pandemic response in New South Wales, Australia. (4th July 2022) - Shih, Patti; Hallam, Laila; Clay‐Williams, Robyn; Carter, Stacy M.; Brown, Anthony
Abstract: Background: Reflections on the response to the COVID‐19 pandemic often evoke the concept of 'resilience' to describe the way health systems adjusted and adapted their functions to withstand the disturbance of a crisis, and in some cases, improve and transform in its wake. Drawing from this, this study focuses on the role of consumer representatives in healthcare services in initiating changes to the way they participated in the pandemic response in the state of New South Wales in Australia. Methods: In‐depth interviews were conducted with two cohorts of consumer representatives. Cohort A included experienced and self‐identified consumer leaders, who worked together in a COVID‐19 Consumer Leaders Taskforce ; Cohort B included participants outside of this group, and purposively included consumer representatives from rural and regional areas, and culturally and linguistically diverse communities. Results: The pause in consumer engagement to support health service decision‐making in responding to the pandemic forced consumer representatives to consider alternative approaches to participate. Some initiated networking with each other, forming new collaborations to produce consumer‐led research and guidelines on pandemic‐related patient care. Others mobilized support from community and politicians to lobby for specific healthcare issues in their local areas. Conclusion: The response to the COVID‐19 pandemic made visible the brittle nature of previous engagement processes of involving consumers in organizational design and governance. However, the momentum for proactive self‐organization in an unexpected crisis created space for consumer representatives to reset and reimagine their role as active partners in health services. Their ability to adapt and adjust ways of working are key assets for a resilient health system. Patient or Public Contribution: This project is a collaborative study between academic researchers and health consumer (patient and public) representatives. It followed the principles of codesign and coresearch, whereby both consumer representatives and academic researchers contributed equally to all stages of the project. The study was cofunded by both academic institutions and consumer representative organizations.